Exploring the relationship between R&D investment and the labour market outcomes in the OECD countries - Woźniak-Jasińska, Katarzyna; Lewoniewski, Włodzimierz (Research Papers in Economics and Finance, 2025)
This paper examines the relationship between labour market outcomes, labour market policies, and investment in R&D in OECD countries from 2011 to 2021. Firstly, the relationships between labour market variables and R&D investment variables were estimated using Pearson correlation. Subsequently, predictive models were developed using eight algorithms to assess their performance in explaining labour market outcomes. K-fold cross-validation was employed to average results over multiple train/test splits. Initial findings indicate that R&D investment was positively associated with the employment rate and labour force participation rate, and negatively associated with the unemployment rate. Furthermore, public spending on active labour market policies showed a significant association with R&D investment variables. Additionally, findings based on the performance of predictive models revealed that data on R&D investment and labour market outcomes exhibit complex interactions best captured by ensemble techniques – Random Forest and Gradient Boosting. Regardless of the model used, the strictness of employment protection for temporary contracts consistently emerged as an important predictor for all labour market outcomes. Moreover, indicators related to R&D investment demonstrated relatively strong predictive power, suggesting a meaningful contribution of such investment to employment outcomes. Innovation-related measures also emerged as relevant factors influencing labour market outcomes in OECD countries.